2017
DOI: 10.1074/jbc.m117.806075
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a highly selective chemical inhibitor of matrix metalloproteinase-9 (MMP-9) that allosterically inhibits zymogen activation

Abstract: Aberrant activation of matrix metalloproteinases (MMPs) is a common feature of pathological cascades observed in diverse disorders, such as cancer, fibrosis, immune dysregulation, and neurodegenerative diseases. MMP-9, in particular, is highly dynamically regulated in several pathological processes. Development of MMP inhibitors has therefore been an attractive strategy for therapeutic intervention. However, a long history of failed clinical trials has demonstrated that broad-spectrum MMP inhibitors have limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 60 publications
3
96
0
Order By: Relevance
“…Although results from early animal studies utilizing broad spectrum inhibitors were compelling, it was determined that inhibiting such a broad scale inhibition of MMPs interfered with normal tissue function, which could support disease progression (66, 67). Moreover, MMP-9 active site inhibitors were prone to off target binding which induced unexpected malignancies including musculoskeletal toxicity (68).…”
Section: Discussionmentioning
confidence: 99%
“…Although results from early animal studies utilizing broad spectrum inhibitors were compelling, it was determined that inhibiting such a broad scale inhibition of MMPs interfered with normal tissue function, which could support disease progression (66, 67). Moreover, MMP-9 active site inhibitors were prone to off target binding which induced unexpected malignancies including musculoskeletal toxicity (68).…”
Section: Discussionmentioning
confidence: 99%
“…None of the 50some clinical trials with MMP inhibitors were successful, due to off-target toxicity or absence of efficacy. A recent study reports effective allosteric prevention of pro-MMP-9 activation in a mouse neuroinflammatory model by a small, highly selective heterocyclic chemical inhibitor [204]. This orally administered compound does not prevent activation of the structurally related pro-MMP-2, and does not inhibit catalytically active MMP-1, −2, −3, −9 or −14.…”
Section: Proteolysis-related Processes As Drug Targetsmentioning
confidence: 99%
“…Additional allosteric, exosite and effector-binding site interactions are expected to contribute significantly to exclusive selection of the target protease. Structural conservation of the specificity site throughout a protease family with diverse catalytic properties and biological targets may pose a problem in designing specific drugs, and a promising alternative was developed by targeting zymogen activation rather than the active protease [204]. A highly selective compound that allosterically inhibits MMP-9 activation by binding to a pocket near the zymogen cleavage site may be a first viable drug candidate.…”
Section: The Future Of Proteolysis-related Drug and Diagnostic Develomentioning
confidence: 99%
“…C, the chemical structure of compound JNJ0966. D, a novel approach by Scannevin et al (9), in which the MMPI (green) targets the final activation point of the zymogen and prevents prodomain (blue) removal. This MMPI does not inhibit the mature MMP.…”
Section: Figure 1 Mechanisms Of Mmp Inhibitorsmentioning
confidence: 99%
“…As one role of MMPs in cancer is associated with excessive activity, blocking zymogen activation could provide a fairly targeted mechanism to disrupt cancer development. The conceptually simple but elegant working hypothesis, then, of Scannevin et al (9), is that repressing activation of the zymogen could be an alternate approach to preventing activity. Using high-throughput screening employing the ThermoFluor approach, which reports on protein stability variations due to ligand binding, the authors identified compound JNJ0966 (Fig.…”
mentioning
confidence: 99%